1982
DOI: 10.1007/bf00636182
|View full text |Cite
|
Sign up to set email alerts
|

Keratinolytic fungi in Egyptian soils

Abstract: The frequency of occurrence of keratinolytic fungi in seventy soil samples collected from different sites in Upper Egypt and in the coastal area of the Mediterranean and baited with human and animal hair and pigeon feathers was determined. Twenty-one species in addition to an unidentified species, which belong to sixteen genera were collected. Chrysosporium indicum, B. tropicum, C. keratinophilum and Microsporum gypseum were the most frequent fungal species recovered from baited soils. The eight soil samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Compared to C. indicum, C. tropicum Carmichael has a wider global distribution (1)(2)(3)(4)10,14,18,20,30,33). The two along with M. gypseum appeared to be good keratinophiliccompetiters as was indicated by their growth on all the substrates in primary soil cultures.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Compared to C. indicum, C. tropicum Carmichael has a wider global distribution (1)(2)(3)(4)10,14,18,20,30,33). The two along with M. gypseum appeared to be good keratinophiliccompetiters as was indicated by their growth on all the substrates in primary soil cultures.…”
Section: Discussionmentioning
confidence: 93%
“…Amongst the Chrysosporium species, C. keratinophilum (Frey) Carmichael was the second commonest. It was first reported in soils ofAustralia&NewGuinea (16) andisnow known to occur in many parts ofEurope, Asia, America, Africaand Easter Island (1,2,8,11,15,18,23,32,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…were also found earlier in the New Valley, Western desert, Egypt, but again at different incidences from those reported here (Abdel-Hafez et al 2000). These fungi have been isolated, at varying frequencies, from soils collected from the Delta area and Upper Egypt (Abdel-Fattah et al 1982;Abdel-Mallek et al 1989;Abdel-Hafez et al 1989;Youssef et al 1989;Karam El-Din et al 1990;Maghraby 1994;Gherbawy 1999;Abdel-Raouf 2000;Abdel-Hafez et al 2000).…”
Section: Seasonal Variations Of Floor Dust Fungi In Qenamentioning
confidence: 97%
“…Absence of skin lesions in them is not necessarily proof of absence of a dermatophytic infeo tion as there may be numerous healthy carriers (6). (4,8,13,15,17), locations highly frequented by animals and/or man contain a higher population of keratinophilic hngi than remote or desert areas (1,8,30). previous studies described keratinophilic hngi observed in areas frequented only or chiefly by man (5,7,9,11,20), by man and animals (15,16,19), by only animals (18,26,31).…”
Section: Introductionmentioning
confidence: 99%